Epidemiological and clinical study of cases of endemic pemphigus foliaceus and pemphigus vulgaris in a reference center in the state of Minas Gerais, Brazil - Vanessa Martins Barcelos; Everton Carlos Siviero do Vale; Marcelo Grossi Araujo; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background: Pemphigus constitutes a group of autoimmune bullous diseases. A reduction in the incidence of endemic pemphigus foliaceus and an increase in pemphigus vulgaris has been described, but there are no studies in Minas Gerais that address the subject. Objective: To describe the epidemiological and clinical profile of patients with pemphigus treated at the Dermatology Service of a public University Hospital in the state of Minas Gerais, Brazil. Methods: An observational, descriptive, and cross-sectional study was carried out of cases of endemic pemphigus foliaceus and pemphigus vulgaris, for a period of six months. A questionnaire was filled out with epidemiological and clinical data on the disease. Results: A total of 122 patients were included in the study, 64 with endemic pemphigus foliaceus and 58 with pemphigus vulgaris. When comparing patients with endemic pemphigus foliaceus and those with pemphigus vulgaris, a statistical difference was observed between the median age of initial disease manifestation (p = 0.001), patient occupation (p = 0.010), area of residence (p = 0.000), forests (p = 0.000) and rivers/streams close to the dwelling (p = 0.001) and the number of systemic medications required to control the disease (p = 0.002). When comparing patients with endemic pemphigus foliaceus to those evaluated in a study carried out at the same service in 2008, there was a statistical difference in the area of residence (p = 0.030). Study limitations: The assessed population comes from a tertiary care service that is not a reference for the entire state. Conclusions: Patients with endemic pemphigus foliaceus and pemphigus vulgaris maintain statistically significant differences regarding their main variables in the literature, such as age and area of residence. Historically, there has been a reduction in cases of endemic pemphigus foliaceus and an increase in cases of pemphigus vulgaris in this population.